Palliative Care in Advanced Dementia - Eisenmann, Yvonne; Golla, Heidrun; Schmidt, Holger; Voltz, Raymond; Perrar, Klaus Maria (Frontiers in Psychiatry, 2020)
Dementia syndrome is common and expected to increase significantly among older people and characterized by the loss of cognitive, psychological and physical functions. Palliative care is applicable for people with dementia, however they are less likely to have access to palliative care. This narrative review summarizes specifics of palliative care in advanced dementia. Most people with advanced dementia live and die in institutional care and they suffer a range of burdensome symptoms and complications. Shortly before dying people with advanced dementia suffer symptoms as pain, eating problems, breathlessness, neuropsychiatric symptoms and complications as respiratory or urinary infections and frequently experience burdensome transitions. Pharmacological and nonpharmacological interventions may reduce symptom burden. Sensitive observation and appropriate assessment tools enable health professionals to assess symptoms and needs and to evaluate interventions. Due to lack of decisional capacity proxy decision making is often necessary. Advanced care planning is an opportunity establishing values and preferences and is associated with comfort and decrease of burdensome interventions. Family carers are important for people with advanced dementia they also experience distress and are in need for support. Recommendations refer to early integration of palliative care, recognizing signs of approaching death, symptom assessment and management, advanced care planning, person-centered care, continuity of care, and collaboration of health care providers.